2017
DOI: 10.2147/ijn.s142912
|View full text |Cite
|
Sign up to set email alerts
|

A charge-reversible nanocarrier using PEG-PLL(-<em>g</em>-Ce6, DMA)-PLA for photodynamic therapy

Abstract: A polyelectrolyte nanoparticle composed of PEG-PLL(- g -Ce6, DMA)-PLA was developed for nanomedicinal application in photodynamic therapy. These nanoparticles formed stable aggregates through the hydrophobic interaction of poly(lactic acid) and demonstrated pH-dependent behaviors such as surface charge conversion and enhanced cellular uptake at acidic pH, resulting in improved phototoxicity. In vivo animal imaging revealed that the prepared PEG-PLL(- g -Ce6, DMA)-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 49 publications
(58 reference statements)
0
15
0
Order By: Relevance
“…In recent years, various polyelectrolyte nanoparticles composed of, for example, chitosan, poly(2-acrylamido-2-methylpropanesulfonic acid), poly-l-lysine (PLL) and poly(ethylene glycol)-poly(llysine)-poly(lactic acid), have been explored as promising carriers for the delivery of anticancer compounds, such as curcumin, 10 doxorubicin 11 or camptothecin, 12 as well as photosensitizers for photodynamic therapy. 13 Our previous studies pointed to the polyelectrolyte nanocapsules formed by encapsulation of nanoemulsion droplets in multilayer shells of poly-amino acids, namely PLL and PGA, as a promising candidate for a drug delivery system. We characterized nanoparticles similar in size, but differing in charge and surface decoration with PEG and found that both negatively charged as well as close to neutral, PEGylated empty polyelectrolyte nanocapsules did not affect the viability of various cell types.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, various polyelectrolyte nanoparticles composed of, for example, chitosan, poly(2-acrylamido-2-methylpropanesulfonic acid), poly-l-lysine (PLL) and poly(ethylene glycol)-poly(llysine)-poly(lactic acid), have been explored as promising carriers for the delivery of anticancer compounds, such as curcumin, 10 doxorubicin 11 or camptothecin, 12 as well as photosensitizers for photodynamic therapy. 13 Our previous studies pointed to the polyelectrolyte nanocapsules formed by encapsulation of nanoemulsion droplets in multilayer shells of poly-amino acids, namely PLL and PGA, as a promising candidate for a drug delivery system. We characterized nanoparticles similar in size, but differing in charge and surface decoration with PEG and found that both negatively charged as well as close to neutral, PEGylated empty polyelectrolyte nanocapsules did not affect the viability of various cell types.…”
Section: Introductionmentioning
confidence: 99%
“…The Ce6 was conjugated with the positively charged hydrophilic PEG-PLL di-block copolymer using DCC and NHS chemistry and confirmed by 1 H NMR (Figure 4a). Due to the presence of three ionizable carboxyl groups in Ce6, the solubility of free Ce6 changes with the pH of the aqueous solution [32,33]. The free Ce6 aggregates or precipitates under acidic conditions, whereas the solubilized monomeric Ce6 is predominant with an increase in pH.…”
Section: Resultsmentioning
confidence: 99%
“…This can be contributed to the inertness of DMA and SA groups on the side of PLL at pH 7.4 as demonstrated by previous studies. 28,[31][32][33]40 However, under an acidic condition, the zeta potential of DA-ss-DT and DA-cc-DT rapidly changed from negative to positive, and after incubation of 90 minutes, the zeta potentials of DA-ss-DT and DA-cc-DT were 20.3±0.8 and 19.5±0.7 mV, respectively ( Figure 3B). This is ascribed to the hydrolysis of DMA-derived amides of PLL in response to the acidic environment.…”
Section: Surface Charge Conversion Behavior Of Da-ss-dtmentioning
confidence: 99%
“…PEG-b-PLL was synthesized by ring opening polymerization of Lys-NCA using mPEG-NH 2 as a macroinitiator according to the previous studies. 17,21,31 Briefly, Lys-NCA (3.93 g, 1.2 mM) was dissolved in 60 mL of dry DMF. Then, mPEG-NH 2 (2.0 g, 0.4 mM) was dissolved in 50 mL of dry DMF as the macroinitiator and added to Lys-NCA solution via a syringe under dry argon.…”
Section: Synthesis Of Peg-b-pll Block Copolymermentioning
confidence: 99%
See 1 more Smart Citation